2019
DOI: 10.1016/j.ecresq.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Family-centered measures of access to early care and education

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…van Ham and Mulder (2005) found that spatial access to childcare affects maternal employment; mothers are more likely to work when there is a higher per capita number of childcare seats within a 10-min driving radius. In the most sophisticated GIS-based study to date, Davis et al (2019) calculated adjusted supply, driving time, cost, and quality of ECE services within a 20-min drive from the estimated location of children's homes. They found driving times to be shorter, and both price and quality to be higher in the urban capital compared to the rest of their state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…van Ham and Mulder (2005) found that spatial access to childcare affects maternal employment; mothers are more likely to work when there is a higher per capita number of childcare seats within a 10-min driving radius. In the most sophisticated GIS-based study to date, Davis et al (2019) calculated adjusted supply, driving time, cost, and quality of ECE services within a 20-min drive from the estimated location of children's homes. They found driving times to be shorter, and both price and quality to be higher in the urban capital compared to the rest of their state.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we developed a spatially-based measure of ECE affordability that combines information about the number of ECE seats located within a reasonable distance to the family's home, competition for these seats, and the cost burden to parents to purchase these ECE services. By incorporating information about individual family residences, this "family-centered" approach (Davis et al 2019;Friese et al 2017) reflects the everyday, practical reality of family life. Because the measure is spatially-based, it can be mapped to show how neighborhoods vary on a continuum from low to high accessibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, even prior to the pandemic, families faced a dearth of affordable, high-quality options, with disproportionate impacts on black, indigenous, and other people of color (BIPOC), as well as other historically marginalized populations [7]. Due to structural racism and systemic discrimination, childcare deserts, or areas with low supply or shortages of childcare [8], are disproportionately located in BIPOC, rural, tribal, and low-income communities [7]. In 2016, only 57% of surveyed parents of young children reported having good childcare choices where they live [9].…”
Section: Introductionmentioning
confidence: 99%
“…Lower-income communities are more likely than others to face particularly high hurdles in providing an adequate supply of ECE programs. Many low-income families cannot afford to pay market-rate fees for ECE, and lowincome communities may not have substantial public or philanthropic revenue streams, creating lower supply in poor places (Council of Economic Advisors 2014; Malik et al 2018;Davis, Lee, and Sojourner 2019;Chaudry et al 2021). Additionally, consistent with evidence that greater spatial access to social service programs is associated with higher rates of participation among low-income households (Allard, Tolman, and Rosen 2003;Herbst and Tekin 2016), we should expect that a greater local supply of ECE programs and resources will correspond to higher rates of participation.…”
mentioning
confidence: 99%